Changes in Parental Perceptions of Their Care of Their Children's Oral Health From Age 1 to 4 Years - Jeanette M. Daly; Steven M. Levy; Yinghui Xu; Richard D. Jackson; George J. Eckert; Barcey T. Levy; Margherita Fontana (SAGE Publishing, 2019)
Introduction: In this 3-year longitudinal study, parent/child attended 3 dental visits and in between, parents were called every 4 months and asked if their child had visited the dentist and if fluoride varnish had been applied. Methods: Objectives were to assess changes in parents' perceptions of how well they do in taking care of their children's teeth and/or gums across these 3 time points (at age 1, 2.5, and 4 years), assess differences in parents' perceptions of how well they do taking care of their children's teeth and/or gums versus taking care of their children's medical health, and determine factors associated with parental perceptions of how well they do in taking care of the children's teeth and/or gums longitudinally. Results: Participant pairs (1325) were enrolled and over time there was a significant improvement in parental perceptions of their job taking care of their children's teeth and/or gums, increasing from 86% perceiving it to be excellent/very good/good at their child's 1 year of age to 92% at child's age 4 years. The estimated odds of parents perceiving they provided excellent/very good/good versus fair/poor care for the children's teeth and/or gums were higher for those who cleaned and checked inside the children's mouth and/or gums daily (odds ratio 4.74) or took their children to the dentist yearly or twice yearly (odds ratio; 2.73). Conclusions: Parents' perceptions of the care of their children's teeth and/or gums improved over time. Parents consistently perceived that they provided better medical care than dental care for their child.